Mechanization: a must for African agriculture - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
Human muscle-power alone can no longer feed Africa's growing population. Farmers will have to mechanize or food production will continue to fail to keep up with population growth. Mechanization does not mean simply the introduction of tractors...